Bacteriological Profile of Urinary Tract Infection of Children at GMC Teaching Hospital - Shrestha, SP; Shrestha, AK; Lamsal, L; Joshi, M (Journal of Chitwan Medical College, 2013)
This study aimed to find bacterial profile of urinary tract infection (UTI) in children between 2 months to 15 years of age. This is a hospital based retrospective study conducted at Gandaki medical college and teaching hospital, Pokhara over a period of 18 months. Among the total 575 children enrolled for the study, 110 children (19.1%) were found to be culture positive. Most common age group having culture positivity is 1-5 years (40%). Present study showed that UTI is more common in girls (69.1%) than in boys (30.9%). E. coli was still the most commonly isolated bacteria (70.9%) followed by Proteus (20%), Klebsiella (5.4%) and Pseudomonas sp. in (1.8%). E. coli was sensitive to Nitrofurantoin (84.6 %), Amikacin (80.7%), Gentamicin (73%) and Ofloxacin in (53.8%). Most commonly used drugs for the treatment of UTI like Cefixime and Ceftriaxone was sensitive only in 15% and 10% respectively. Similarly, Klebsiella was sensitive to Amikacin and Gentamicin (100%) but sensitive to Nitrofurantoin in only 66% of cases. Proteus was sensitive to Nitrofurantoin (95.4%), Amikacin (86%) and to Gentamicin (59%). High resistance rate was observed to Cefixime and Ceftriaxone, the commonly used drugs for its treatment in OPD basis. DOI: http://dx.doi.org/10.3126/jcmc.v3i3.8633 Journal of Chitwan Medical College 2013; 3(3): 22-25